2020
DOI: 10.1038/s41598-019-56061-2
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Hemodynamic Risk Factors for Middle Cerebral Artery Aneurysm: a Case-Control Study of 190 Patients

Abstract: this study analyzed morphometric and hemodynamic parameters of aneurysmal and non-aneurysmal middle cerebral artery (McA) bifurcations and their relationship with optimal values derived from the principle of minimum work (PMW). The study included 96 patients with MCA aneurysm and 94 controls. Aneurysm patients presented with significantly higher values of the radius and cross-sectional area of the McA trunk, angle between the post-bifurcation branches (α angle) and volume flow rate (VFR) and had significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 38 publications
(59 reference statements)
3
22
0
Order By: Relevance
“…Moreover, the parent vessel diameter was also one of the independent factors associated with the occurrence of IAs. These results are consistent with our previous report in which we showed that a larger radius of the parent MCA vessel was associated with a signi cant increase in the volume ow rate (VFR) (31). We also showed that VFR was a factor independently associated with the formation of MCA aneurysms.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, the parent vessel diameter was also one of the independent factors associated with the occurrence of IAs. These results are consistent with our previous report in which we showed that a larger radius of the parent MCA vessel was associated with a signi cant increase in the volume ow rate (VFR) (31). We also showed that VFR was a factor independently associated with the formation of MCA aneurysms.…”
Section: Discussionsupporting
confidence: 93%
“…We also showed that VFR was a factor independently associated with the formation of MCA aneurysms. Of note, the comparison of blood velocity values for the parent MCA vessel performed in this study did not show differences between those patients with MCA aneurysms and the controls (31).…”
Section: Discussionmentioning
confidence: 46%
“…The WSS experienced at a bifurcation is dependent on its geometry, including the radii of all the vessels involved and the bifurcation angle of the arterial tree [45,46]. The increase in the asymmetry of the vascular diameters of bifurcations and the values of the bifurcation angles, and the decrease in the bilateral angles formed between the daughter and parent vessels and the inclination angle (formed between the parent vessel axis and the plane containing the axes of the two daughter vessels) likely contribute to abnormally enhanced haemodynamic stresses at the arterial bifurcations [26,[47][48][49][50][51][52][53]. Thus, arterial morphology and local haemodynamics are interrelated: the geometry directly determines the bloodflow parameters, while the flow drives arterial wall remodelling which determines the future geometry, promoting aneurysm formation.…”
Section: Discussionmentioning
confidence: 99%
“…All CT studies were performed using a 64-row 128-slice CT system (GE Optima CT 660, GE Healthcare, USA) using the parameters previously described [ 26 ]. On average, 50 ml of ionic contrast material (Iomeron 350, Bracco Imaging Deutschland GmbH, Konstanz, Germany) was injected into the basilic vein at 4–4.5 ml/sec via a selectively positioned catheter with the aid of an automatic syringe (OptiVantage DH, Mallincrodt, St Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The MCA is also a location of saccular cerebral aneurysms [3][4]. Aneurysms of the MCA are most often located within its main trunk division where hemodynamic stress is greatest [4][5].…”
Section: Introductionmentioning
confidence: 99%